2008
DOI: 10.1186/1471-2164-9-370
|View full text |Cite
|
Sign up to set email alerts
|

Differential control of Zap1-regulated genes in response to zinc deficiency in Saccharomyces cerevisiae

Abstract: Background: The Zap1 transcription factor is a central player in the response of yeast to changes in zinc status. We previously used transcriptome profiling with DNA microarrays to identify 46 potential Zap1 target genes in the yeast genome. In this new study, we used complementary methods to identify additional Zap1 target genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
108
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(123 citation statements)
references
References 49 publications
14
108
1
Order By: Relevance
“…Several candidate Zap1 target genes encode proteins with roles in protein homeostasis, including a molecular chaperone (HSP26), and proteins involved in autophagy (ATG19, ATG41, and UTH1) and vacuolar proteolysis (PRB1, PRC1, and PEP4) (11). By functional genomics analysis, we also identified genes that were important for survival in low zinc but were not known Zap1 targets (23).…”
Section: Fet4mentioning
confidence: 93%
See 1 more Smart Citation
“…Several candidate Zap1 target genes encode proteins with roles in protein homeostasis, including a molecular chaperone (HSP26), and proteins involved in autophagy (ATG19, ATG41, and UTH1) and vacuolar proteolysis (PRB1, PRC1, and PEP4) (11). By functional genomics analysis, we also identified genes that were important for survival in low zinc but were not known Zap1 targets (23).…”
Section: Fet4mentioning
confidence: 93%
“…Analysis of the Zap1 regulon revealed that zinc-regulated genes can be sorted into two basic classes: "homeostatic" genes induced to maintain intracellular zinc supply and "adaptive" genes that may aid the survival of deficient cells without altering zinc status (11). Homeostatic genes include those required for zinc uptake across the plasma membrane (ZRT1, ZRT2, and * This work was supported by National Institutes of Health Grant GM056285.…”
mentioning
confidence: 99%
“…In fission yeast Schizosaccharomyces pombe, responses to low and high levels of peroxide are modulated by Pap1 and Atf1, respectively (33). Differential activation of target genes by a single regulator (Zap1) in response to zinc deficiency has been reported in Saccharomyces cerevisiae (34), where the elucidation of an underlying mechanism is awaited. Activity modulation through two regulatory metal-binding sites in Zur extends the versatility of this regulator to allow graded expression of target genes in response to expanded concentration ranges of zinc.…”
Section: Graded Expression Of Metal-sensitive Genes In Accordance Withmentioning
confidence: 99%
“…Zap1 plays a central role in the homeostatic regulation of this essential yet potentially toxic metal ion. Under conditions where zinc is limiting, Zap1 activates expression of ϳ80 target genes in the yeast genome (11,12). When cells are zinc-replete, Zap1 function is shut off (13).…”
mentioning
confidence: 99%